Molecular mechanisms of cis-oxygen bridge neonicotinoids to Apis mellifera Linnaeus chemosensory protein: Surface plasmon resonance, multiple spectroscopy techniques, and molecular modeling - Xiangshuai Li; Shiyu Li; Yang Liu; Li Cui; Daibin Yang; Shuning Chen; Xusheng Shao; Huizhu Yuan; Xiaojing Yan (Ecotoxicology and Environmental Safety)
Honeybees, essential pollinators for maintaining biodiversity, are experiencing a sharp population decline, which has become a pressing environmental concern. Among the factors implicated in this decline, neonicotinoid pesticides, particularly those belonging to the fourth generation, have been the focus of extensive scrutiny due to their potential risks to honeybees. This study investigates the molecular basis of these risks by examining the binding interactions between Apis mellifera L. chemosensory protein 3 (AmelCSP3) and neonicotinoids with a cis-oxygen bridge heterocyclic structure. Employing surface plasmon resonance (SPR) in conjunction with multispectral techniques and molecular modeling, this study meticulously analyzed the binding affinity, specificity, and kinetics under conditions that simulate real-world exposure scenarios. Key parameters such as the number of binding sites (n), binding constants (Ka), dissociation constants (KD), and binding distances (r) were quantitatively assessed. The findings revealed that hydrogen bonding and hydrophobic interactions serve as the primary forces driving the binding process, with fluorescence quenching mechanisms involving both dynamic and static interactions. Molecular docking and dynamics simulations further illustrated the stability of these interactions within the active site of the protein. Of particular interest, cis-structured neonicotinoids demonstrated distinct binding characteristics compared to their trans-structured counterparts, including an inverse relationship between the binding constant and temperature. These findings offer critical insights for the design of cis-structured neonicotinoid compounds that are safer for pollinators, thus reducing the impact on non-target organisms such as bees. Furthermore, this research enhances the understanding of the interaction mechanisms between cis-structured neonicotinoid substances and honeybee proteins, providing a foundation for future studies on the environmental safety of these compounds.